The Implementation of The Negativa Non Sunt Probanda Principle in Indonesian Civil Litigation: An Analysis of Banten High Court Decision Number 109/PDT/2022/PT BTN - Muhammad Sulhan; Umar Haris Sanjaya (Universitas Muhammadiyah Tangerang, 2026)
In the Indonesian legal system, civil procedural law pays great attention to the principles underlying decision making by judges in civil cases. One of the principles regulated in civil law is the principle of negativa non sunt probanda, which is often understood as the principle that states that